Modernism : keywords - Cuddy-Keane, Melba; Adam Hammond; Alexandra Peat (Chichester, West Sussex : Wiley-Blackwell, 2014)
'Modernism: Keywords presents a series of short entries explaining the diverse and often contradictory meanings of words used with frequency and urgency in'written modernism'--
Includes bibliographical references and index.
Keywords: English language -- Etymology; English language -- Glossaries, vocabularies, etc; Modernism (Literature); Social structure -- Terminology; Culture -- Terminology; Sociolinguistics; Vocabulary